Farmers’ behavior towards risks of shallot farming: a case study in Kalisoro village, Tawangmangu district, Karanganyar regency, Central Java - Sriyadi (EDP Sciences, 2021)
This study aimed to analyze the level of risk of shallot farming income, investigate the behavior of farmers on the risk of shallot farming, and find out the factors which could influence the farmers’ Behaviors on the risk of shallot farming. This research was conducted by surveying interviews with farmers and related parties as well as field observations. The results showed that shallot farming had a fairly high variation or risk of income. The majority of farmers have adverse behavior towards the risk of shallot farming. The wider the area of land was, the older the farmer was, and the more often they failed so that as a result, the greater the farmer's aversion to risk was faced. Meanwhile, the higher the education level, the more experienced shallot farming, the greater the number of family members, and the higher the income from farming, the smaller the risk aversion of farmers was faced as well. The research results showed that the risk of shallot farming income was greater because of variations in production process. The difference of production variation due to the planting of shallots not simultaneously, so it was recommended that farmers should plant the shallots on time and simultaneously.